Armed conflict, peace audit and early warning 2014 : stability and instability in South Asia : contemporary life in South Asia - Suba Chandran, D.; Chari, P. R. (Armed Conflict, Peace Audit and Early Warning., 2015)
Addressing the gap between the end of violence and the response to peace, the volume assesses whether peace processes are fragile in South Asia.